تجليات المصطلحات الدينية العربية في النصوص الشعرية الملايوية لحمزة الفنصوري - Faizarul Azwan Maskan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
In the text of the Malay poem of Hamzah al-Fansuri collected by G.W. Drewes and L.F Brakel, there are aspects of his poem that related to Islam, Iman and Ihsan in terms of Arabic words, Quranic verses and Prophetic texts. This research exmines the theory of manifestation (Tajalliyat) in Hamzah al-Fansuri's views pertaining to his explanation of non-heterodoxy and non-atheism by dividing the religious Arabic terms used in his poetry to the values of Islam, Iman and Ihsan. This study can be referred to by beginners or anyone who wants to know about him. The research also looks into the biography of Hamzah al-Fansuri and his writings, his views on Islam, Iman and Ihsan, and explains the use of religious terms in his poetry in terms of these three values.